Dual Action of the PN159/KLAL/MAP Peptide: Increase of Drug Penetration across Caco-2 Intestinal Barrier Model by Modulation of Tight Junctions and Plasma Membrane Permeability - Alexandra Bocsik; Ilona Gróf; Lóránd Kiss; Ferenc Ötvös; Ottó Zsíros; Lejla Daruka; Lívia Fülöp; Monika Vastag; Ágnes Kittel; Norbert Imre; Tamás A. Martinek; Csaba Pál; et al. (MDPI AG, 2019)
The absorption of drugs is limited by the epithelial barriers of the gastrointestinal tract. One of the strategies to improve drug delivery is the modulation of barrier function by the targeted opening of epithelial tight junctions. In our previous study the 18-mer amphiphilic PN159 peptide was found to be an effective tight junction modulator on intestinal epithelial and blood⁻brain barrier models. PN159, also known as KLAL or MAP, was described to interact with biological membranes as a cell-penetrating peptide. In the present work we demonstrated that the PN159 peptide as a penetration enhancer has a dual action on intestinal epithelial cells. The peptide safely and reversibly enhanced the permeability of Caco-2 monolayers by opening the intercellular junctions. The penetration of dextran molecules with different size and four efflux pump substrate drugs was increased several folds. We identified claudin-4 and -7 junctional proteins by docking studies as potential binding partners and targets of PN159 in the opening of the paracellular pathway. In addition to the tight junction modulator action, the peptide showed cell membrane permeabilizing and antimicrobial effects. This dual action is not general for cell-penetrating peptides (CPPs), since the other three CPPs tested did not show barrier opening effects.